Unravelling the Distinctive Virulence Traits and Clonal Relationship among the Pseudomonas aeruginosa Isolates from Diabetic Patients - Sarika Suresh; Kattapuni Suresh Prithvisagar; Ballamoole Krishna Kumar; Ramya Premanath (Journal of Pure and Applied Microbiology, 2022)
Infections with P. aeruginosa are three times more common in people with diabetes than in non-diabetic individuals. Investigations disclosing the distinguishing traits of P. aeruginosa strains to cause respiratory and wound infection in diabetics is limited. Wound swab and sputum from infected diabetic patients were used for the isolation of P. aeruginosa. The confirmed isolates were evaluated for their virulence factor production, antibiotic susceptibility, and clonal relationship. The study confirmed the increased virulence of sputum isolates characterized by their multidrug resistant nature, strong biofilm formation at 72h [(p<0.05) =0.003)] and 96h [(p<0.05) =0.002)] and elaboration of proteolytic enzymes (40.0%). Albeit the fact that wound isolates were less virulent than the sputum isolates, there was an increased siderophore production (77.0%). Nearly 90.0% of the isolates including sputum and wound were resistant to colistin. Random Amplified Polymorphic DNA analysis showed no distinct lineages of wound and sputum isolates. The study disclosed the higher prevalence of virulent P. aeruginosa in causing infection in the diabetics. No distinct lineages of the wound and sputum isolates indicated their ability to adapt to different host environments. To the best of our knowledge, this is the first study to show the difference in virulence traits among the P. aeruginosa strains isolated from sputum and wound of diabetic patients. Our study distinctly reveals the significance of periodic examination of antibiotic resistance and virulence factors of P. aeruginosa in order to recognize the possible co-regulatory mechanism involved in their expression.